Kinetics of thermal degradation of a Japanese oil sand - Olalekan S. Alade; Kyuro Sasaki; Yuichi Sugai; Kojo T. Konadu; Eric O. Ansah; Bayo Ademodi; Ryo Ueda (Egyptian Journal of Petroleum)
Thermal degradation characteristics of a Japanese oil sand at different heating rates (10, 20, and 30 °C/min), and 30 ml/min air flow rate have been investigated. The kinetic parameters have been calculated based on three stages of weight loss and/or the conversion of the sample. These include, stage 1 (SI): volatilization of moisture content and the light hydrocarbon (20–227 °C), stage 2 (SII): combustion of heavy hydrocarbon (227–527 °C), and stage 3 (SIII): oxidative decomposition of carbonaceous organic matter (502–877 °C). The results showed that the rate of change of the oil sand conversion with time dαdt was affected by the heating rate. The time taken by the system to reach 0.99 conversion was observed as 85, 50, and 35 min at the heating rates of 10, 20, and 30 °C/min, respectively. The frequency factor, A, at SI was between 0.09 and 0.54 min−1, while the activation energy, Ea, was 11.2–12.5 KJmol−1 (the percentage weight loss, Wt, was 0–3.6 %w/w; and the conversion, α, was 0–0.2.). At SII, the values of A and Ea were 2.1–5.5 min−1 and 17.6–19 KJmol−1, respectively (Wt = 3.1–15.88 %w/w; α = 0.17–0.86.). The value of A at SIII was 5.5E11–1.1E13 min−1, while Ea was 160–200 KJmol−1 (Wt = 15.33–17.99 %w/w; and α = 0.84–0.99). Keywords: Thermogravimetric and differential thermal analysis (TG-DTA), Thermal degradation, Heating rates, Kinetics parameters